RETRACTED: Kanan et al. Empowering Low- and Middle-Income Countries to Combat AMR by Minimal Use of Antibiotics: A Way Forward. Antibiotics 2023, 12, 1504 - Mohammed Kanan; Maali Ramadan; Hanan Haif; Bashayr Abdullah; Jawaher Mubarak; Waad Ahmad; Shahad Mari; Samaher Hassan; Rawan Eid; Mohammed Hasan; Mohammed Qahl; Atheer Assiri; et al. (Antibiotics)
The journal retracts the article “Empowering Low- and Middle-Income Countries to Combat AMR by Minimal Use of Antibiotics: A Way Forward” [...]